2016
DOI: 10.1111/flan.12178
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the OPI and the OPIc: The Effect of Test Method on Oral Proficiency Scores and Student Preference

Abstract: While studies have been done to rate the validity and reliability of the Oral Proficiency Interview (OPI) and Oral Proficiency Interview–Computer (OPIc) independently, a limited amount of research has analyzed the interexam reliability of these tests, and studies have yet to be conducted comparing the results of Spanish language learners who take both exams. For this study, 154 Spanish language learners of various proficiency levels were divided into two groups and administered both the OPI and OPIc within a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…In particular, the OPI and the OPIc result in rather similar scores for candidates who sit for both exams. However, Thompson et al () found that learners tended to score higher on the OPIc than on the OPI in Spanish. In spite of the generally higher scores given to students on the OPIc, they held a less favorable opinion of asynchronous, monologic interface.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…In particular, the OPI and the OPIc result in rather similar scores for candidates who sit for both exams. However, Thompson et al () found that learners tended to score higher on the OPIc than on the OPI in Spanish. In spite of the generally higher scores given to students on the OPIc, they held a less favorable opinion of asynchronous, monologic interface.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Thompson, Cox, and Knapp () compared Spanish learners’ preferences and performances on the OPI and OPIc in order to establish the concurrent validity of the OPIc. When analyzing data from 154 examinees who completed both the OPI and OPIc exams in Spanish within 3 weeks of each other, the researchers found that 54.5% ( n = 84) of 154 OPIs and OPIcs resulted in the exact same ratings with 13.6% ( n = 21) of examinees scoring higher on the OPI and 31.8% ( n = 49) scoring higher on the OPIc (pp.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, test designers still need a robust plan to make a solid validity argument: that is, that the scores from the standardized tests are interpreted correctly and applied appropriately. Applied linguists and educators must continually question, as researchers have (e.g., Bachman, 1988;Clark & Clifford, 1988;Loomis, 2015;Malone, 2003;Thompson, Cox, & Knapp, 2016;Weir, 2005) the following: Are the ways in which ACTFL standardized test scores are used appropriate? Are score interpretations meaningful?…”
Section: What Is the Future Role Of Self-assessment?mentioning
confidence: 99%
“…In an attempt to help instructors understand differences in levels, Liskin-Gasparro (1996) analyzed the communication strategies of IH and Advanced Low (AL) Spanish speakers and found that the AL speakers used a broader range of communicative strategies; however, she did not analyze other aspects of the interview samples and did not look at the differences among the Intermediate sublevels. Apart from this study, most of the research has focused on learners' expected proficiency outcomes at particular points in their program of study (Carroll, 1967;Chambless, 2012;Glisan & Foltz, 1998;Gouoni & Feyten, 1999) or has compared learners' results on the two alternate forms of the assessment, the OPIc and the OPI (Surface, Poncheri, & Bhavsar, 2008;SWA Consulting, 2009;Thompson, Cox, & Knapp, 2016). In contrast, this The degree to which the examinee completed the task presented as defined by the major level Text type Text length The extent to which the amount of language completed the function of the task (words and phrases, sentences, strings of sentences, or connected paragraphs) Discourse organization…”
Section: Introductionmentioning
confidence: 99%